Inclusive Digital Communication in Higher Education: Information Accessibility for Low Vision Students in Bandung Raya - A Hasan Al Husain; Ramona Blanes (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2025)
Inclusive higher education in Indonesia still faces significant challenges in providing accessible digital communication for students with low vision. Learning Management Systems (LMS) are not only repositories of course content but also key mediated communication channels where lecturers, institutions, and students exchange information and feedback. When these platforms are inaccessible, the problem becomes communication inequality that restricts students’ rights to receive and express information. This study explores accessibility barriers experienced by low vision students in universities across Bandung Raya, focusing on their interaction with LMS interfaces, messages, and media formats. Using a constructivist paradigm and an intrinsic case study approach, data were collected through semi-structured interviews and analyzed with Miles and Huberman’s interactive model. Findings reveal three main communication-related accessibility issues: inconsistent visual layout and low-contrast interfaces, inadequate keyboard-based navigation, and the absence of screen reader integration and alternative formats such as audio or transcripts. Viewed through inclusive communication and the social model of disability, these barriers act as structural “noise” in mediated interaction. The study argues that LMS accessibility must be treated as a central component of inclusive digital communication, requiring user-informed design, assistive communication technologies, and participatory testing with low vision students as co-designers.